Gender and German colonialism intimacies, accountabilities, intersections - Zhang, Chunjie; Krimmer, Elisabeth 1967- (Routledge, 2024)
"This book addresses the intersection between gender and colonialism primarily in German colonialism. Gender and German Colonialism is concerned with colonialism as a historical phenomenon and with the repercussions and transformations of the colonial era in contemporary racist and sexist discourses and practices relating to refugees, migrants, and people of non-European descent living in Europe. This volume contributes to the broader effort of decolonization with particular attention to concepts of gender. Rather than focus on only one European empire, it discusses and compares multiple former colonial powers in context. In addition to German colonialism, some chapters focus on the role of gender in Dutch and Belgian colonialism in Indonesia, Africa, and the Americas. This volume will be of value to students and scholars interested in women's and gender studies, social and cultural history, and imperial and colonial history"--
Keywords: Geschichte; Deutsch; Niederländisch; Afrika -- Motiv; Kulturvermittlung; Frau; Kolonie; Weiblichkeit -- Motiv; Literatur; Schriftstellerin; Frau -- Motiv; Kolonialismus -- Motiv; Deutschland; Afrika; German literature / 19th century / History and criticism; German literature / 20th century / History and criticism; Imperialism in literature; Colonies in literature; Women in literature; Literature / Women authors / History and criticism; Women / Germany / Colonies / Social conditions; Germany / Colonies / Race relations; Littérature allemande / 19e siècle / Histoire et critique; Littérature allemande / 20e siècle / Histoire et critique; Impérialisme dans la littérature; Colonies dans la littérature; Femmes dans la littérature; Écrits de femmes / Histoire et critique; Aufsatzsammlung